Ternary positive electrode material and preparation method thereof, positive electrode and lithium ion battery

By using a combination technology of boron nitride coating and lithium borate on the ternary positive electrode material, the problem of insufficient circulation and safety performance of the material is solved, higher structural stability and circulation stability are achieved, and the sensitivity to environmental humidity is reduced.

CN115472802BActive Publication Date: 2025-05-02HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211255453.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-13
Publication Date
2025-05-02
Estimated Expiration
2042-10-13

AI Technical Summary

Technical Problem

The existing ternary cathode materials have shortcomings in circulation performance, safety performance and storage performance, especially the problems of water absorption and short cycle life caused by high nickel materials.

Method used

The boron nitride coating layer is used to stably coat the surface of the positive electrode substrate. Combined with the use of lithium borate, the ternary positive electrode material is formed by dry mixing and calcining treatment, controlling the residual alkali content and optimizing the particle dispersion.

Benefits of technology

The structural stability and cyclic stability of the ternary positive electrode material are improved, the DC internal resistance growth rate under low temperature conditions is reduced, the safety is enhanced, and the storage performance of the material and the smoothness of the coating process are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115472802B_ABST
    Figure CN115472802B_ABST
Patent Text Reader

Abstract

The present invention provides a ternary cathode material, a preparation method thereof, a cathode and a lithium-ion battery. The ternary cathode material includes a cathode substrate and a coating layer coated on the surface of the cathode substrate. The chemical formula of the cathode substrate is Li a Ni x Co y Mn 1‑x‑y O2, where 1.01 ≤ a ≤ 1.2, 0.6 < x < 1, 0 < y < 0.1. The coating layer includes boron nitride. The content of residual alkali LiOH on the surface of the ternary cathode material is 0.04 to 0.20 wt%, and the content of residual alkali Li2CO3 is 0.03 to 0.20 wt%. While the above ternary cathode material can overcome the defects of traditional cathode materials such as high impedance, small Li + migration rate, and poor power performance at low temperature and high rate, it shows a low DCR growth rate during the cycling process at low temperature conditions and can timely dissipate the heat generated by the lithium-ion battery, improving the safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a ternary positive electrode material and a preparation method thereof, a positive electrode and a lithium ion battery. Background Art

[0002] The positive electrode materials of lithium-ion batteries can be divided into three categories: the first category is lithium nickel oxide (LiNiO2), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), lithium iron phosphate (LiFePO4) and other monovalent transition metal oxide positive electrode materials; the second category is lithium nickel cobalt oxide (LiNi x Co 1-x O2), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O2) and other binary transition metal oxide positive electrode materials; the third type is lithium nickel cobalt manganese oxide (NCM: LiNi x Co y Mn 1-x-y O2, x+y+z=1), lithium nickel cobalt aluminum oxide (NCA: LiNi x Co y AlzO2, x+y+z=1) and other ternary transition metal oxide positive electrode materials. Among the first type of positive electrode materials, LiCoO2 has good cycle performance, LiNiO2 has high specific capacity, and LiMnO2 has high safety and low cost. The performance of nickel cobalt manganese oxide lithium ternary positive electrode material is a material with good development prospects. It is a type of material that can be balanced and regulated in terms of specific capacity, cyclability, safety and cost. Specifically, in the ternary material LiNi x Co y Mn 1-x-y In O2, the Ni element is more active and can significantly increase the capacity of the electrode material; the Co element inhibits the mixing of lithium and nickel to a certain extent and strengthens the layered structure, and some Co contributes to the capacity of the electrode material; during the electrochemical charge and discharge process, the valence of the Mn element remains basically unchanged, which not only stabilizes the structure of the material but also reduces the cost of the material.

[0003] Although ternary materials have a great advantage over other cathode materials in terms of energy density, they also have some disadvantages, such as easy deviation from the stoichiometric ratio during the synthesis process, phase change during the cycle process, etc., which lead to poor cycle performance, safety performance and storage performance of ternary materials. In particular, high-nickel materials hinder the large-scale application of ternary cathode materials in the field of power batteries. The higher the proportion of nickel in the ternary cathode material, the higher the discharge capacity of the material and the higher the residual alkali. As a result, the cycle life becomes shorter during the charge and discharge process. In particular, the interface stability between the active material and the electrolyte will also deteriorate accordingly, causing side reactions and affecting the cycle stability of the material. Based on many studies, the main problems of ternary cathode materials are: (1) cation mixing or lithium-nickel mixing; (2) poor thermal stability; (3) unstable surface structure; (4) strain and microcracks in secondary particles; (5) excessive surface alkali content. At present, the modification methods of ternary cathode materials include: element doping, surface coating, design of gradient materials and electrolyte additives, etc. The key to improving the performance of ternary positive electrode materials is to increase the electronic conductivity of the material, reduce the impedance of the material during the insertion and deinsertion process, and form a coating layer on the surface of the material to enhance the stability of the surface layer in contact with the electrolyte solution.

[0004] The mainstream coating technologies for ternary positive electrode materials are divided into two categories: dry and wet. Wet treatment of ternary positive electrode materials will cause the NCM particles to absorb water and form NiOOH-like impurities on the surface of the material. The NiOOH phase will decompose during the subsequent heating and drying process, forming an oxygen-deficient layer on the surface of the NCM particles, resulting in an increase in the material interface impedance. The wet treatment process will bring negative effects. For example, the wet coating process is complex, which can easily cause the loss of lithium in the bulk phase of the material and lead to a decrease in specific capacity. In addition, ternary positive electrode materials, especially high-nickel ternary NCM / NCA materials, are easy to absorb moisture in the air due to the high content of residual alkali LiOH and Li2CO3 impurities (>0.7wt%), resulting in side reactions, producing residual alkali and metal oxides, which reduce the capacity of high-nickel materials and deteriorate the cycle performance. The high residual alkali makes the ternary positive electrode material very easy to absorb moisture (absorb water) during the process of making batteries and the configuration of slurry, which makes the slurry appear jelly, and then makes the slurry unable to be coated. In addition, the subsequent large amount of moisture absorption by the pole piece will also lead to a sharp decline in battery performance, which greatly reduces the industrialization of lithium-ion batteries, especially high-nickel ternary positive electrode materials. Therefore, in addition to strictly controlling the moisture in the environment during the production process of the materials, the humidity of the general high-nickel ternary positive electrode materials must be strictly controlled during the entire processing process of the lithium battery (dew point must be lower than -40°C), which will bring high energy consumption to the manufacture of the battery cell (electricity consumption caused by moisture control in the dry room). Therefore, solving the water absorption problem of ternary positive electrode materials, especially high-nickel ternary positive electrode materials, while meeting the electrochemical performance requirements is the key research and development direction, and ultimately solving the problem of high-nickel ternary positive electrode material slurry coating process and later pole piece storage.

[0005] When a lithium-ion battery is charged for the first time, lithium ions will continuously escape from the positive electrode, but when it is discharged, the lithium ions cannot be completely embedded and reset, which causes lithium ion loss and irreversible capacity loss of the battery. Therefore, the initial efficiency of the material is related to the structure of the material itself, the kinetic factors of the material, and the side reactions under high potential. Under the condition of high cut-off voltage and high charge and discharge rate, fluoride corrosion and transition metal dissolution will occur on the surface of the positive electrode material, causing the structure of the positive electrode surface material to collapse, resulting in the deterioration of the battery cycle. Therefore, high voltage has an important correlation with the structural integrity and surface properties of the ternary positive electrode material.

[0006] The particle dispersion of single crystal ternary cathode materials is an important technical indicator. If there is agglomeration between particles, it will be difficult to evenly disperse the conductive agent in the slurry mixing process of the battery manufacturing process, and eventually some particles will not be able to obtain uniform conductive agent on the surface, affecting the lithium ion diffusion path. This will inevitably lead to the deterioration of the overall electronic conductivity of the battery cell pole piece, especially the impact on the battery cycle performance is particularly obvious. After a certain period of cycling, the capacity retention rate of the battery made of this cathode material will decrease sharply.

[0007] DC internal resistance is one of the important electrical properties of lithium-ion batteries. The DC internal resistance (DC impedance) of lithium-ion batteries is referred to as DCR, including charging DCR and discharging DCR. DCR is an important indicator for evaluating the performance of lithium-ion batteries, and directly affects the energy density and cycle life of lithium-ion batteries. Among them, reducing the DCR of the battery and improving its kinetic performance are effective ways to achieve its high power performance. Discharging DCR and charging DCR are both important performance indicators of lithium-ion batteries. Charging DCR reflects the charging polarization size and charging heat generation capacity of the battery cell, while discharging DCR reflects the polarization and heat generation capacity of the battery cell in the discharge state. Under normal circumstances, the internal resistance of the battery will increase sharply in a low temperature environment, thereby reducing the discharge capacity and rate performance of the battery, and low temperature will also cause lithium precipitation. The precipitation of metal lithium dendrites may pierce the diaphragm and affect the safety performance of the battery. Improving the lithium ion solid phase transmission capacity of the positive electrode material can significantly improve the interface resistance of the positive electrode material and the DCR performance of the battery. The DCR during the non-cycling process is the short-term DCR of the battery cell. Due to the short time, there is less polarization accumulation, side reaction accumulation, etc. The DCR after cycling reflects the long-term DCR of the battery cell, which is a comprehensive situation of the battery cell's ohmic internal resistance, polarization accumulation, side reaction accumulation, electrode health status, etc. If the DCR has a sudden change, it is often accompanied by a deterioration in the cycle performance. Summary of the invention

[0008] The main purpose of the present invention is to provide a ternary positive electrode material and a preparation method thereof, a positive electrode and a lithium ion battery, so as to solve the problem of poor cycle performance of lithium ion batteries in the prior art.

[0009] In order to achieve the above object, according to one aspect of the present invention, a ternary positive electrode material is provided, the ternary positive electrode material comprises a positive electrode substrate and a coating layer coated on the surface of the positive electrode substrate, the chemical formula of the positive electrode substrate is Li a Ni x Co y Mn 1-x-y O2, wherein 1.01≤a≤1.2, 0.6<x<1, 0<y<0.1, the coating layer includes boron nitride, and the content of residual alkali LiOH on the surface of the ternary positive electrode material is 0.04~0.20wt%, and the content of residual alkali Li2CO3 is 0.03~0.20wt%.

[0010] Furthermore, the coating layer further comprises lithium borate, and preferably the molar ratio of the positive electrode substrate, boron nitride and lithium borate is 100:0.02-0.5:0.03-0.5, and preferably the boron nitride is amorphous.

[0011] Furthermore, the D50 particle size of the above-mentioned ternary positive electrode material is between 2.50 and 4.50 μm.

[0012] According to another aspect of the present invention, there is provided a method for preparing the aforementioned ternary positive electrode material, the preparation method comprising: step S1, in an atmosphere containing methane, subjecting a sol comprising a nickel source, a cobalt source, a manganese source, a lithium source, and a water-soluble carbon source to a first insulation treatment according to the ratio of elements in the ternary positive electrode material to obtain an insulation treated material; step S2, in an oxygen-containing atmosphere, subjecting the insulation treated material to a second insulation treatment to obtain a positive electrode substrate; step S3, dry mixing the positive electrode substrate with a boron-containing precursor to obtain a dry mixture; step S4, in an inert gas atmosphere comprising a nitrogen-containing element or a reducing gas atmosphere comprising a nitrogen-containing element, subjecting the dry mixture to a calcination treatment to obtain a ternary positive electrode material, wherein the temperature of the first insulation treatment is greater than the temperature of the second insulation treatment.

[0013] Further, in the above step S1, the volume content of methane in the methane-containing atmosphere is preferably 10-50%, and the methane-containing atmosphere preferably includes a mixed gas of methane, nitrogen, argon, and helium; the temperature of the first heat preservation treatment is preferably 500-900° C., and the time of the first heat preservation treatment is preferably 3-5 hours; the process of forming the sol preferably includes: mixing raw materials including a nickel source, a cobalt source, a manganese source, a lithium source, and a water-soluble carbon source to form a raw material solution; evaporating the solvent from the raw material solution to form a sol; the mass of the water-soluble carbon source is preferably 0.1-5wt% of the total mass of the metal source in the raw material solution; the water-soluble carbon source is preferably selected from any one or more of glucose, sucrose, citric acid, and starch; the raw material is preferably The total concentration of metal ions in the solution is 1 to 15 mol / L, the nickel source preferably includes a metal salt of divalent nickel, and the nickel source is preferably selected from any one or more of nickel nitrate, nickel sulfate, nickel chloride, and nickel acetate; the cobalt source preferably includes a metal salt of divalent cobalt, and the cobalt source is preferably selected from any one or more of cobalt nitrate, cobalt sulfate, cobalt chloride, and cobalt acetate; the manganese source preferably includes a metal salt of divalent manganese, and the manganese source is preferably selected from any one or more of manganese nitrate, manganese sulfate, manganese chloride, and manganese acetate; the lithium source is preferably selected from any one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium chloride, lithium phosphate, and dilithium hydrogen phosphate; the temperature for evaporating the solvent is preferably 40 to 90° C., and the time for evaporating the solvent is preferably 1 to 24 hours.

[0014] Furthermore, in the above step S2, the temperature of the second heat preservation treatment is 300-600°C, the time of the second heat preservation treatment is preferably 5-10 hours, and the volume content of oxygen in the oxygen-containing atmosphere is preferably 30-99.9%.

[0015] Furthermore, in the above step S3, dry mixing is performed by fluidized bed airflow mill coating, and the conditions for fluidized bed airflow mill coating are preferably: the carrier gas includes argon, carbon dioxide and nitrogen, the volume content of carbon dioxide in the carrier gas is 1-20%, the water content of the carrier gas is 1000-5000ppm, the gas flow rate is 100-20000mL / min, and the dry mixing time is 1-5min; in terms of boron element, the molar number of the boron-containing precursor is 0.05-1% of the total molar number of metal elements in the positive electrode substrate, and the boron-containing precursor is preferably selected from any one or more of boric acid, boron trioxide and ammonia borane.

[0016] Furthermore, in the above step S4, the calcination temperature is 300-600° C., and the calcination time is preferably 1-5 hours.

[0017] According to another aspect of the present invention, there is provided a positive electrode, comprising a positive electrode material, wherein the positive electrode material comprises the aforementioned ternary positive electrode material.

[0018] According to another aspect of the present invention, there is provided a lithium ion battery comprising a positive electrode and a negative electrode, wherein the positive electrode is the positive electrode described above.

[0019] By applying the technical solution of the present invention, the boron nitride of the above-mentioned ternary positive electrode material of the present application is stably coated on the surface of the positive electrode substrate, which can avoid direct contact between the positive electrode and the electrolyte, and inhibit the positive electrode failure caused by intergranular cracking caused by micro-strain during repeated lithium insertion and extraction during charging and discharging, thereby improving the structural stability of the ternary positive electrode material, thereby ensuring the cycle stability of the ternary positive electrode material. In addition, thanks to the good thermal conductivity and ion conductivity of boron nitride, on the one hand, it can overcome the high impedance and Li+ of traditional positive electrode materials at low temperature and high rate. + Defects such as low migration rate and poor power performance of the material cause it to exhibit a lower DCR growth rate during the cycle under low temperature conditions. On the other hand, it can dissipate the heat generated by the lithium-ion battery in time, thereby improving safety.

[0020] Among them, a lower residual alkali content is beneficial to inhibiting the escape of lattice oxygen, thereby ensuring the specific capacity and cycle performance of the ternary positive electrode material on the one hand, and on the other hand reducing the requirements of the ternary positive electrode material on environmental humidity during use, thereby improving the storage performance of the ternary positive electrode material. A lower residual alkali content facilitates the smooth completion of the coating process of the positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0022] Figure 1A SEM image of a ternary positive electrode material provided according to Example 1 of the present invention is shown;

[0023] Figure 2 The XRD diagram of a ternary positive electrode material provided according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0025] As analyzed in the background technology of this application, the prior art has the problem of poor cycle performance of lithium-ion batteries. In order to solve this problem, this application provides a ternary positive electrode material and a preparation method thereof, a positive electrode and a lithium-ion battery.

[0026] In a typical embodiment of the present application, a ternary positive electrode material is provided, the ternary positive electrode material comprises a positive electrode substrate and a coating layer coated on the surface of the positive electrode substrate, the chemical formula of the positive electrode substrate is Li a Ni x Co y Mn 1-x-y O2, wherein 1.01≤a≤1.2, 0.6<x<1, 0<y<0.1, the coating layer includes boron nitride, and the content of residual alkali LiOH on the surface of the ternary positive electrode material is 0.04~0.20wt%, and the content of residual alkali Li2CO3 is 0.03~0.20wt%.

[0027] The boron nitride of the above-mentioned ternary positive electrode material of the present application is stably coated on the surface of the positive electrode substrate, which can avoid direct contact between the positive electrode and the electrolyte, and inhibit the positive electrode failure caused by intergranular cracking caused by micro-strain during repeated lithium insertion and extraction during charging and discharging, thereby improving the structural stability of the ternary positive electrode material, thereby ensuring the cycle stability of the ternary positive electrode material. In addition, thanks to the good thermal conductivity and ion conductivity of boron nitride, on the one hand, it can overcome the high impedance and Li+ of traditional positive electrode materials at low temperature and high rate. + Defects such as low migration rate and poor power performance of the material cause it to exhibit a lower DCR growth rate during the cycle under low temperature conditions. On the other hand, it can dissipate the heat generated by the lithium-ion battery in time, thereby improving safety.

[0028] Among them, a lower residual alkali content is beneficial to inhibiting the escape of lattice oxygen, thereby ensuring the specific capacity and cycle performance of the ternary positive electrode material on the one hand, and on the other hand reducing the requirements of the ternary positive electrode material on environmental humidity during use, thereby improving the storage performance of the ternary positive electrode material. A lower residual alkali content facilitates the smooth completion of the coating process of the positive electrode sheet.

[0029] In one embodiment of the present application, the coating layer further comprises lithium borate, and preferably the molar ratio of the positive electrode substrate, boron nitride and lithium borate is 100:0.02-0.5:0.03-0.5, and preferably the boron nitride is amorphous.

[0030] As a fast ion conductor, lithium borate can effectively increase the migration rate of lithium ions and improve ion conductivity. The above preferred ratio can make boron nitride and lithium borate more fully synergistic, so that the final ternary positive electrode material has better initial capacity, cycle performance and other electrical properties.

[0031] In one embodiment of the present application, the D50 particle size of the above-mentioned ternary positive electrode material is between 2.50 and 4.50 μm.

[0032] The ternary positive electrode material of the present application is a single crystalline material, which is easier to break into fine grains of the above-mentioned size. The uniform particles are more suitable for use as positive electrode materials for lithium-ion batteries.

[0033] In another typical embodiment of the present application, a method for preparing the aforementioned ternary positive electrode material is provided, and the preparation method comprises: step S1, in an atmosphere containing methane, subjecting a sol including a nickel source, a cobalt source, a manganese source, a lithium source, and a water-soluble carbon source to a first insulation treatment according to the element ratio in the ternary positive electrode material to obtain an insulation treated material; step S2, in an oxygen-containing atmosphere, subjecting the insulation treated material to a second insulation treatment to obtain a positive electrode substrate; step S3, dry mixing the positive electrode substrate with a boron-containing precursor to obtain a dry mixture; step S4, in an inert gas atmosphere including a nitrogen-containing element or a reducing gas atmosphere including a nitrogen-containing element, subjecting the dry mixture to a calcination treatment to obtain a ternary positive electrode material, wherein the temperature of the first insulation treatment is greater than the temperature of the second insulation treatment.

[0034] On the one hand, the gradient heat preservation treatment can effectively reduce the residual alkali content on the surface of the material as a mild modification method, inhibit the lattice oxygen from being released and causing the failure of the positive electrode material, thereby improving the electrochemical properties and process performance of the positive electrode material of the lithium ion battery. On the other hand, a carbonized layer (amorphous carbon) can be formed on the particle surface of the heat-insulated material through step S1, thereby hindering the agglomeration of the particles, and then facilitating the formation of fine grains with good dispersibility and uniform dispersion of the raw materials including the metal source during the sintering process, and further, providing a basis for the subsequent calcination treatment to form a single crystal material without agglomeration, so that the final formed material is easier to break. Through steps S3 and S4, a coating layer including boron nitride can be formed in situ on the positive electrode substrate to obtain a ternary positive electrode material with a suitable size and good single crystal morphology. And the ternary positive electrode material prepared by this method has good electrochemical properties, and the preparation method is simple to operate, has strong feasibility, high safety, and is easy to industrialize.

[0035] In one embodiment of the present application, in the above step S1, the volume content of methane in the methane-containing atmosphere is preferably 10-50%, and the methane-containing atmosphere preferably includes a mixed gas of methane, nitrogen, argon, and helium; the temperature of the first insulation treatment is preferably 500-900°C, and the time of the first insulation treatment is preferably 3-5h; the process of forming a sol preferably includes: mixing raw materials including a nickel source, a cobalt source, a manganese source, a lithium source, and a water-soluble carbon source to form a raw material solution; evaporating the solvent from the raw material solution to form a sol; the mass of the water-soluble carbon source is preferably 0.1-5wt% of the total mass of the metal source in the raw material solution; the water-soluble carbon source is preferably selected from any one or more of glucose, sucrose, citric acid, and starch; Preferably, the total concentration of metal ions in the raw material solution is 1 to 15 mol / L, and the nickel source preferably includes a metal salt of divalent nickel, and the nickel source is preferably selected from any one or more of nickel nitrate, nickel sulfate, nickel chloride, and nickel acetate; the cobalt source preferably includes a metal salt of divalent cobalt, and the cobalt source is preferably selected from any one or more of cobalt nitrate, cobalt sulfate, cobalt chloride, and cobalt acetate; the manganese source preferably includes a metal salt of divalent manganese, and the manganese source is preferably selected from any one or more of manganese nitrate, manganese sulfate, manganese chloride, and manganese acetate; the lithium source is preferably selected from any one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium chloride, lithium phosphate, and dilithium hydrogen phosphate; the temperature for evaporating the solvent is preferably 40 to 90° C., and the time for evaporating the solvent is preferably 1 to 24 hours.

[0036] In addition, the lithium source taken according to the element ratio in the ternary positive electrode material is relatively large. On the one hand, the excess lithium can compensate for the volatilization of lithium during the first insulation treatment and the second insulation treatment, and on the other hand, it can form a lithium borate fast ion conductor with the boron-containing precursor, thereby increasing the migration rate of lithium ions, improving the ion conductivity, and increasing the conductivity of lithium ions while reducing the residual alkali on the surface of the ternary positive electrode material.

[0037] The above preparation method generally further includes cooling, grinding and screening the positive electrode substrate after the first heat preservation treatment and the second heat preservation treatment.

[0038] Methane is used to control the carbonization of the water-soluble carbon source to form a carbonized layer on the surface of the material particles. The preferred atmosphere containing methane, the preferred temperature and time of the first heat preservation treatment, and the preferred type and content of the water-soluble carbon source can form a more uniform carbonized layer on the surface of the material particles, thereby facilitating a more complete coating of the surface of the material particles to prevent the agglomeration of the material particles. The preferred process of forming a sol by evaporating the solvent is more conducive to quickly and easily obtaining the positive electrode substrate by the sol-sol method, wherein the heating evaporation can be specifically carried out in the form of a normal pressure water bath.

[0039] The growth of positive electrode material particles requires an oxidizing environment. The presence of a carbonized layer can prevent particle agglomeration. This process consumes the carbonized layer as the positive electrode material particles grow into a single crystal morphology. In order to further improve the efficiency of the formation of the ternary positive electrode material and obtain a ternary positive electrode material with a good single crystal morphology as much as possible, it is preferred that in the above step S2, the temperature of the second insulation treatment is 300-600°C, the time of the second insulation treatment is preferably 5-10 hours, and the volume content of oxygen in the oxygen-containing atmosphere is preferably 30-99.9%.

[0040] In one embodiment of the present application, in the above-mentioned step S3, dry mixing is performed by fluidized bed airflow mill coating, and the conditions for fluidized bed airflow mill coating are preferably: the carrier gas includes argon, carbon dioxide and nitrogen, the volume content of carbon dioxide in the carrier gas is 1-20%, the water content of the carrier gas is 1000-5000ppm, the gas flow rate is 100-20000mL / min, and the dry mixing time is 1-5min; in terms of boron element, the molar number of the boron-containing precursor is 0.05-1% of the total molar number of metal elements in the positive electrode substrate, and the boron-containing precursor is preferably selected from any one or more of boric acid, boron trioxide and ammonia borane.

[0041] The residual alkali on the surface of the ternary material is generally generated at the corners and edges of the particles, and then gradually diffuses to the surface of the particles. The amount and time of contact with water vapor can determine the amount and generation position of the residual alkali on the surface of the ternary material. The carbon dioxide in the carrier gas can react with the residual lithium on the surface of the positive electrode material to generate lithium carbonate. During the reaction, lithium borate is generated where the residual alkali exists, thereby achieving the purpose of in-situ coating. A certain amount of B element is retained in the ternary material to delay the migration of lithium ions in the bulk phase to further form residual alkali.

[0042] The present invention uses a trace amount of water at the ppm level to help control the amount and rate of residual alkali formation and further react with the boron-containing material to form fast ion conductor lithium borate in situ after subsequent calcination treatment.

[0043] Preferably, in the above step S4, the calcination temperature is 300-600° C., and the calcination time is preferably 1-5 hours, which is helpful to quickly form a stable boron nitride coating layer.

[0044] In another typical embodiment of the present application, a positive electrode is provided, comprising a positive electrode material, wherein the positive electrode material comprises the above-mentioned ternary positive electrode material.

[0045] The ternary positive electrode material obtained by the above modification is used as the positive electrode material, so that the corresponding positive electrode has excellent electrical properties such as capacity and cycle retention rate.

[0046] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode and a negative electrode, wherein the positive electrode is the positive electrode mentioned above.

[0047] The lithium-ion battery including the above-mentioned positive electrode has electrical properties such as higher capacity, cycle retention rate, and lower growth rate of DCR value at low temperature.

[0048] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0049] Example 1

[0050] (1) Nickel sulfate, cobalt sulfate, manganese sulfate, and lithium hydroxide were weighed according to a molar ratio of nickel element, manganese element, cobalt element, and lithium element of 0.65:0.08:0.27:1.02, and dissolved in deionized water to obtain 100 mL of a mixed solution of nickel salt, cobalt salt, manganese salt, and lithium salt, wherein the molar concentration of nickel sulfate was 0.65 mol / L, the molar concentration of cobalt sulfate was 0.08 mol / L, the molar concentration of manganese sulfate was 0.27 mol / L, and the molar concentration of lithium hydroxide was 1.02 mol / L.

[0051] Glucose in an amount of 1 wt% of the total mass of nickel salt, cobalt salt, manganese salt and lithium salt was added to the mixed solution, the mixture was evenly mixed, and heated in a water bath at 50°C for evaporation for 3 h to form a sol; the sol was then subjected to a first insulation treatment at 700°C for 3 hours in a gas atmosphere with a methane volume content of 30% (a mixed gas of methane, nitrogen, argon and helium; unless otherwise specified, the following embodiments and comparative examples all use these types of gases) to obtain an insulation-treated material.

[0052] (2) The heat-treated material was subjected to a second heat-treatment at 300° C. for 5 hours in an oxygen-rich atmosphere with an oxygen volume content of 30%, cooled, and ground through a 300-mesh sieve to obtain a positive electrode substrate.

[0053] (3) Boric acid and the positive electrode substrate are dry mixed by fluidized bed jet mill coating in a molar ratio of 0.2:100 between boron and all metal elements (nickel, cobalt, manganese, lithium) in the positive electrode substrate. The conditions for fluidized bed jet mill coating are as follows: the carrier is a mixed gas of argon, carbon dioxide, and nitrogen, wherein the volume concentration of carbon dioxide is 5%, the ratio of argon to nitrogen is 1:1, and the water content of the carrier gas is 1000 ppm; the gas flow rate is 100 mL / min, the mixing time is 5 min, and the coating step is repeated once, i.e., the coating is performed twice in total to obtain a dry mixture.

[0054] (4) In a mixed atmosphere of nitrogen and hydrogen (nitrogen volume concentration is 80%), the dry mixture is calcined at 400°C for 4 hours to obtain a ternary positive electrode material with a D50 particle size of 3.50 μm.

[0055] Example 2

[0056] (1) Nickel sulfate, cobalt sulfate, manganese sulfate, and lithium hydroxide were weighed according to a molar ratio of nickel element, manganese element, cobalt element, and lithium element of 0.72:0.08:0.20:1.05, and dissolved in deionized water to obtain 100 mL of a mixed solution of nickel salt, cobalt salt, manganese salt, and lithium salt, wherein the molar concentration of nickel sulfate was 0.72 mol / L, the molar concentration of cobalt sulfate was 0.08 mol / L, the molar concentration of manganese sulfate was 0.20 mol / L, and the molar concentration of lithium hydroxide was 1.05 mol / L.

[0057] Add sucrose in an amount of 2 wt% of the total mass of nickel salt, cobalt salt, manganese salt and lithium salt to the mixed solution, mix well, and heat and evaporate for 3 hours in a water bath at 50°C to form a sol; then perform a first insulation treatment at 500°C for 5 hours in a gas atmosphere with a methane volume content of 30% to obtain an insulation-treated material.

[0058] (2) The heat-treated material was subjected to a second heat-treatment at 300° C. for 10 hours in an oxygen-rich atmosphere with an oxygen volume content of 70%, cooled, and ground through a 300-mesh sieve to obtain a positive electrode substrate.

[0059] (3) Boric acid and the positive electrode substrate are dry mixed by fluidized bed jet mill coating according to a molar ratio of boron to all metal elements in the positive electrode substrate of 0.15:100. The conditions for fluidized bed jet mill coating are as follows: the carrier is a mixed gas of argon, carbon dioxide, and nitrogen, wherein the volume concentration of carbon dioxide is 10%, the ratio of argon to nitrogen is 1:1, and the water content of the carrier gas is 5000 ppm; the gas flow rate is 500 mL / min, the mixing time is 5 min, and the coating step is repeated once, i.e., the coating is performed twice in total to obtain a dry mixture.

[0060] (4) In a mixed atmosphere of nitrogen and hydrogen (nitrogen volume concentration is 90%), the dry mixture is calcined at 350° C. for 4 h to obtain a ternary positive electrode material with a D50 particle size of 4.00 μm.

[0061] Example 3

[0062] (1) Nickel sulfate, cobalt sulfate, manganese sulfate, and lithium hydroxide were weighed according to a molar ratio of nickel element, manganese element, cobalt element, and lithium element of 0.72:0.08:0.20:1.05, and dissolved in deionized water to obtain 100 mL of a mixed solution of nickel salt, cobalt salt, manganese salt, and lithium salt, wherein the molar concentration of nickel sulfate was 0.72 mol / L, the molar concentration of cobalt sulfate was 0.08 mol / L, the molar concentration of manganese sulfate was 0.2 mol / L, and the molar concentration of lithium hydroxide was 1.05 mol / L.

[0063] Add citric acid in an amount of 2 wt% of the total mass of nickel salt, cobalt salt, manganese salt and lithium salt to the mixed solution, mix well, and heat and evaporate for 3 hours in a water bath at 50°C to form a sol; then perform a first insulation treatment at 700°C for 5 hours in a gas atmosphere with a methane volume content of 30% to obtain an insulation-treated material.

[0064] (2) The heat-treated material was subjected to a second heat-treatment at 400° C. for 10 hours in an oxygen-rich atmosphere with an oxygen volume content of 90%, cooled, and ground through a 300-mesh sieve to obtain a positive electrode substrate.

[0065] (3) Boric acid and the positive electrode substrate are dry mixed by fluidized bed jet mill coating according to a molar ratio of boron to all metal elements in the positive electrode substrate of 0.15:100. The conditions for fluidized bed jet mill coating are as follows: the carrier is a mixed gas of argon, carbon dioxide, and nitrogen, wherein the volume concentration of carbon dioxide is 20%, the ratio of argon to nitrogen is 1:1, and the water content of the carrier gas is 5000 ppm; the gas flow rate is 1000 mL / min, the mixing time is 3 min, and the coating step is repeated 3 times, i.e., a total of 4 coatings are performed to obtain a dry mixture.

[0066] (4) In a mixed atmosphere of nitrogen and hydrogen (nitrogen volume concentration 90%), the dry mixture was calcined at 350°C for 4 hours to obtain a ternary positive electrode material with a D50 particle size of 4.10 μm.

[0067] Example 4

[0068] (1) Nickel sulfate, cobalt sulfate, manganese sulfate, and lithium hydroxide were weighed according to a molar ratio of nickel element, manganese element, cobalt element, and lithium element of 0.83:0.08:0.09:1.05, and dissolved in deionized water to obtain 100 mL of a mixed solution of nickel salt, cobalt salt, manganese salt, and lithium salt, wherein the molar concentration of nickel sulfate was 0.83 mol / L, the molar concentration of cobalt sulfate was 0.08 mol / L, the molar concentration of manganese sulfate was 0.09 mol / L, and the molar concentration of lithium hydroxide was 1.05 mol / L.

[0069] Add 4 wt% starch in a total mass of nickel salt, cobalt salt, manganese salt and lithium salt to the mixed solution, mix well, and heat and evaporate for 3 hours in a 50°C water bath to form a sol; then perform a first insulation treatment at 650°C for 5 hours in a gas atmosphere with a methane volume content of 10% to obtain an insulation-treated material.

[0070] (2) The heat-treated material was subjected to a second heat-treatment at 400° C. for 10 hours in an oxygen-rich atmosphere with an oxygen volume concentration of 95%, cooled, and ground through a 300-mesh sieve to obtain a positive electrode substrate.

[0071] (3) Boric acid and the positive electrode substrate are dry mixed by fluidized bed jet mill coating according to a molar ratio of boron to all metal elements in the positive electrode substrate of 0.15:100. The conditions for fluidized bed jet mill coating are as follows: the carrier is a mixed gas of argon, carbon dioxide, and nitrogen, wherein the volume concentration of carbon dioxide is 20%, the ratio of argon to nitrogen is 1:1, and the water content of the carrier gas is 5000 ppm; the gas flow rate is 1000 mL / min, the mixing time is 3 min, and the coating step is repeated 3 times, i.e., a total of 4 coatings are performed to obtain a dry mixture.

[0072] (4) In a mixed atmosphere of nitrogen and hydrogen (nitrogen volume concentration 90%), the dry mixture was calcined at 400°C for 5 hours to obtain a ternary positive electrode material with a D50 particle size of 2.50 μm.

[0073] Example 5

[0074] The difference from Example 1 is that the mass of glucose is 0.1wt% of the total mass of nickel salt, cobalt salt, manganese salt and lithium salt, and finally a ternary positive electrode material is obtained.

[0075] Example 6

[0076] The difference from Example 1 is that the mass of glucose is 5wt% of the total mass of nickel salt, cobalt salt, manganese salt and lithium salt, and finally a ternary positive electrode material is obtained.

[0077] Example 7

[0078] The difference from Example 1 is that the mass of glucose is 0.08wt% of the total mass of nickel salt, cobalt salt, manganese salt and lithium salt, and finally a ternary positive electrode material is obtained.

[0079] Example 8

[0080] The difference from Example 1 is that the sol is subjected to a first heat preservation treatment in a gas atmosphere with a methane volume content of 10% to obtain a heat preservation treated material, and finally a ternary positive electrode material is obtained.

[0081] Example 9

[0082] The difference from Example 1 is that the sol is subjected to a first heat preservation treatment in a gas atmosphere with a methane volume content of 50% to obtain a heat preservation treated material, and finally a ternary positive electrode material is obtained.

[0083] Example 10

[0084] The difference from Example 1 is that the sol is subjected to a first heat preservation treatment in a gas atmosphere with a methane volume content of 8% to obtain a heat preservation treated material, and finally a ternary positive electrode material is obtained.

[0085] Embodiment 11

[0086] The difference from Example 1 is that the temperature of the first heat preservation treatment is 900° C., and a ternary positive electrode material is finally obtained.

[0087] Example 12

[0088] The difference from Example 1 is that the temperature of the first heat preservation treatment is 1000° C., and a ternary positive electrode material is finally obtained.

[0089] Example 13

[0090] The difference from Example 1 is that the ternary positive electrode material is finally obtained by heating and evaporating for 3 h in a water bath at 90°C to form a sol.

[0091] Embodiment 14

[0092] The difference from Example 1 is that the temperature of the second heat preservation treatment is 600° C., and a ternary positive electrode material is finally obtained.

[0093] Embodiment 15

[0094] The difference from Example 1 is that the temperature of the second heat preservation treatment is 200° C., and a ternary positive electrode material is finally obtained.

[0095] Example 16

[0096] The difference from Example 1 is that the heat-insulating treated material is subjected to a second heat-insulating treatment in an oxygen-rich atmosphere with an oxygen volume content of 99.9%, and finally a ternary positive electrode material is obtained.

[0097] Embodiment 17

[0098] The difference from Example 1 is that the molar ratio of boron to all metal elements (nickel, cobalt, manganese, lithium) in the positive electrode substrate is 0.05:100, and a ternary positive electrode material is finally obtained.

[0099] Embodiment 18

[0100] The difference from Example 1 is that the molar ratio of boron to all metal elements (nickel, cobalt, manganese, lithium) in the positive electrode substrate is 1:100, and a ternary positive electrode material is finally obtained.

[0101] Embodiment 19

[0102] The difference from Example 1 is that the molar ratio of boron to all metal elements (nickel, cobalt, manganese, lithium) in the positive electrode substrate is 0.03:100, and a ternary positive electrode material is finally obtained.

[0103] Embodiment 20

[0104] The difference from Example 1 is that the calcination temperature is 500° C., and a ternary positive electrode material is finally obtained.

[0105] Embodiment 21

[0106] The difference from Example 1 is that the carrier gas used in the fluidized bed jet mill coating process in (3) is a mixture of nitrogen and argon (the ratio of the two is consistent with that in Example 1), but does not contain carbon dioxide, and finally a ternary positive electrode material is obtained.

[0107] Embodiment 22

[0108] The difference from Example 1 is that the carrier gas used in the fluidized bed jet mill coating step (3) does not contain water, and finally a ternary positive electrode material is obtained.

[0109] Comparative Example 1

[0110] The difference from Example 1 is that glucose is not added in (1), and a ternary positive electrode material is finally obtained.

[0111] Comparative Example 2

[0112] The difference from Example 1 is that the sol is directly subjected to a second heat preservation treatment in oxygen to finally obtain a ternary positive electrode material.

[0113] Comparative Example 3

[0114] The difference from Example 1 is that in (3), conventional grinding and coating procedures (using deionized water as the medium and grinding and coating with a mortar) are used for dry mixing to obtain a dry product, and finally a ternary positive electrode material is obtained.

[0115] Comparative Example 4

[0116] The difference from Example 1 is that the positive electrode substrate is directly used as a ternary positive electrode material.

[0117] Comparative Example 5

[0118] Commercially available nickel cobalt manganese lithium oxide, in which the molar ratio of nickel, cobalt and manganese elements is 0.65:0.08:0.27, is used as a ternary positive electrode material.

[0119] The SEM photo of the ternary cathode material obtained in Example 1 is as follows Figure 1 As shown. Figure 1 It can be seen that the material obtained by the present invention is evenly dispersed, with less agglomeration, and coating particles with uniform particle size and consistent morphology and structure are distributed around the ternary positive electrode material.

[0120] The XRD pattern of the ternary cathode material obtained in Example 1 is as follows Figure 2 As shown. Figure 2 It can be seen that the ternary positive electrode material has a good crystal phase and no impurity peaks. Figure 2The diffraction peaks in the sample are consistent with the characteristic diffraction peaks of the layered α-NaFeO2 structure, proving that the ternary cathode material has a pure α-NaFeO2 phase structure without impurities, indicating that the ternary cathode material has a layered structure. Figure 2 The splitting degree of the two groups of peaks (006) / (102) and (108) / (110) of the ternary positive electrode material is relatively obvious, indicating that the ternary positive electrode material obtained in the present invention has a complete layered structure.

[0121] The mass ratio of the positive electrode substrate, boron nitride and lithium borate in each ternary positive electrode material of the above Examples 1 to 22 and Comparative Examples 1 to 5 is recorded as A, and A and the D50 particle size of each ternary positive electrode material are listed in Table 1.

[0122] Table 1

[0123] Implementation / Comparative Example A D50 particle size / μm Example 1 100:0.1:0.1 3.50 Example 2 100:0.12:0.03 4.00 Example 3 100:0.09:0.06 4.10 Example 4 100:0.09:0.06 2.50 Example 5 100:0.1:0.1 3.50 Example 6 100:0.1:0.1 3.51 Example 7 100:0.1:0.1 4.50 Example 8 100:0.1:0.1 3.53 Example 9 100:0.1:0.1 3.50 Example 10 100:0.1:0.1 4.52 Embodiment 11 100:0.1:0.1 3.51 Example 12 100:0.1:0.1 4.55 Example 13 100:0.1:0.1 3.50 Embodiment 14 100:0.1:0.1 3.52 Embodiment 15 100:0.1:0.1 3.54 Example 16 100:0.1:0.1 3.50 Embodiment 17 100:0.03:0.02 3.53 Embodiment 18 100:0.5:0.5 3.64 Embodiment 19 100:0.02:0.01 3.49 Embodiment 20 100:0.1:0.1 3.55 Embodiment 21 100:0.05:0.15 3.60 Embodiment 22 100:0.05:0.15 3.63 Comparative Example 1 - 3.51 Comparative Example 2 - 3.54 Comparative Example 3 - 3.52 Comparative Example 4 - 3.50 Comparative Example 5 - 3.51

[0124] Residual alkali test:

[0125] Residual alkali test method: weigh the sample according to Table 2, accurate to 0.0001g, place the weighed sample in a 100mL beaker, add 50mL deionized water, put the magnetic beads in the beaker and seal it with plastic wrap, then place the beaker on a magnetic stirrer and stir for about 10 to 15 minutes and remove it; let it stand for 5 minutes, filter it with a glass funnel, and the filtered clear liquid is the test solution.

[0126] Table 2

[0127]

[0128]

[0129] Accurately transfer the solution to be tested into a 100mL beaker, put in a stirring rotor, control the sample volume to about 50mL (make up with water if less than 50mL), place the beaker on the magnetic stirrer of the automatic potentiometric titrator, add phenolphthalein for 2d, select HCl standard solution according to the table and titrate it from red to colorless. The instrument will record the volume Ep1(V1) of HCl standard solution consumed at the stoichiometric point and the pH; then add methyl orange for 2d, continue to titrate it from yellow to orange. The instrument will record the volume Ep2(V2) of HCl standard solution consumed at the stoichiometric point and the pH.

[0130] Analysis results calculation:

[0131] (1) When 2V1>V2, it contains LiOH and Li2CO3, and the calculation formula is as follows:

[0132]

[0133] (2) When 2V1<V2, it contains Li2CO3 and LiHCO3, and the calculation formula is as follows:

[0134]

[0135] (3) When 2V1 = V2, it contains only Li2CO3, and the calculation formula is as follows:

[0136]

[0137] In the above formula: c is the concentration of HCl standard solution (mol / L); V1(Ep1) is the volume of HCl standard solution consumed at the first equivalence point (mL); V2(Ep2) is the volume of HCl standard solution consumed at the second equivalence point (including the first equivalence point) (mL); V' is the volume of the sample solution (mL); V is the volume of the sample (mL); 23.95 is the molar mass of LiOH (g / mol); 73.89 is the molar mass of Li2CO3 (g / mol); 67.96 is the molar mass of LiHCO3 (g / mol); m is the mass of the sample (g).

[0138] The above test results are summarized in Table 3.

[0139] Table 3

[0140]

[0141]

[0142]

[0143] It can be seen from Table 3 and Table 4 that the preparation method of the ternary positive electrode material provided by the present invention can obtain a material with a low residual alkali content. It can be seen from the comparison of Example 1 and Example 2 that the present invention can obtain a positive electrode material with a low residual alkali content by adopting dry mixing. Comparing Example 1, Example 21, and Example 22, it can be seen that the carrier gas in the fluidized bed airflow mill coating condition contains trace moisture at the ppm level, which can promote the lithium ions in the bulk phase to form residual alkali with carbon dioxide in the gas. The residual alkali formed in this process forms fast ion conductor lithium borate in situ after subsequent high-temperature treatment, avoiding the formation of residual alkali during the storage of the material. Comparative Example 3 uses water as a medium. Although it can significantly reduce the residual alkali, it will cause the loss of lithium ions in the material lattice, resulting in an unstable crystal structure, which is similar to water washing or water-based medium coating. It can be seen from the comparison of Example 1 and Example 4 that the calcination treatment step in the present invention can effectively reduce the residual alkali content in the material. The water-soluble carbon (glucose) in Example 7 is outside the value range, which is not conducive to controlling the particle size and also has side effects on the formation of residual alkali on the surface of the material. Example 10 shows that the particle D50 is too large, and the corresponding electrochemical performance is relatively poor. Example 12 has a too high sintering temperature, which causes excessive loss of lithium source during the sintering process. Although the residual alkali is low, high temperature is conducive to the growth of particles, resulting in larger particle size and relatively poor electrochemical performance. Example 15 shows that the second insulation gradient affects the residual alkali content, and the DCR growth rate is high.

[0144] Electrical performance test:

[0145] The ternary positive electrode materials of Examples 1 to 22 and Comparative Examples 1 to 5 were used to assemble CR2016 button cells for electrochemical performance evaluation, respectively. Metal lithium was used as the counter electrode, and the electrode plate ratio was the mass ratio, ternary positive electrode material (NCM): SP conductive agent (graphite): PVDF adhesive (polyvinylidene fluoride) = 80:10:10 (mass percentage); the electrolyte was an EC:DMC (1:1V / V) solution containing 1 mol / L LiPF6, the battery plate was punched into a disc with a diameter of 12 mm, the diameter of the diaphragm used was 19 mm, and the diameter of the negative electrode lithium sheet used was 15 mm.

[0146] Under the test conditions of 2.8-4.4V, the battery capacity, initial efficiency, rate performance and 50-week cycle performance at 1C at 25°C were tested. After the battery was set to 50% SOC at room temperature 25°C and then placed at -20°C for 2 hours, it was discharged at 2C rate for 30s to obtain the DCR value. The test results are shown in Table 4.

[0147] Table 4

[0148]

[0149]

[0150] It can be seen from Table 4 that the ternary positive electrode material prepared by this method has good gram capacity utilization, cycle retention rate, and slow DCR growth rate at low temperature under high voltage conditions (2.8-4.4V). Comparing Example 1 with Comparative Example 1, it can be seen that the addition of a water-soluble carbon source plays an important role in reducing the DCR value of the ternary positive electrode material. Compared with Example 1, the electrochemical performance after wet treatment in Comparative Example 2 is poor. It can be seen that the dry mixing used in the present invention can significantly improve the electrochemical performance of the material. Comparing Example 1 with Example 21 and Example 22, it can be seen that the use of aqueous carrier gas in the coating process of the present invention in conjunction with subsequent high-temperature treatment can promote the formation of lithium borate in the positive electrode material, and the formation of lithium borate has a significant effect on improving the initial efficiency of the material.

[0151] Water absorption test:

[0152] The water absorption verification experiment was conducted on the ternary positive electrode materials prepared in Comparative Example 1 and Example 1 respectively: the samples to be tested were exposed to an environment of 45°C and 60% relative humidity for 12h, 24h, and 48h, and the water content of the samples was tested. The test results are shown in Table 5. Among them, the substrate of Example 1 is the positive electrode substrate of Example 1, and the finished product of Example 1 is the ternary positive electrode material obtained in Example 1.

[0153] Table 5

[0154]

[0155] It can be seen from Table 5 that under long-term high temperature and high humidity environment, the ternary positive electrode material prepared by the present invention has better anti-hygroscopic ability. The active oxygen anions on the surface of the ternary positive electrode material provided by the present invention will react with carbon dioxide and water in the air to form carbonate ions, while lithium ions migrate from the bulk phase to the surface and form residual alkali. This process is accompanied by deoxidation of the material surface to form a structurally distorted surface oxide layer. The above results show that the ternary positive electrode material of the present invention has good anti-water absorption ability, and the material has good lattice stability during storage.

[0156] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0157] The boron nitride of the above-mentioned ternary positive electrode material of the present application is stably coated on the surface of the positive electrode substrate, which can avoid direct contact between the positive electrode and the electrolyte, and inhibit the positive electrode failure caused by intergranular cracking caused by micro-strain during repeated lithium insertion and extraction during charging and discharging, thereby improving the structural stability of the ternary positive electrode material, thereby ensuring the cycle stability of the ternary positive electrode material. In addition, thanks to the good thermal conductivity and ion conductivity of boron nitride, on the one hand, it can overcome the high impedance and Li+ of traditional positive electrode materials at low temperature and high rate. +Defects such as low migration rate and poor power performance of the material cause it to exhibit a lower DCR growth rate during the cycle under low temperature conditions. On the other hand, it can dissipate the heat generated by the lithium-ion battery in time, thereby improving safety.

[0158] Among them, a lower residual alkali content is beneficial to inhibiting the escape of lattice oxygen, thereby ensuring the specific capacity and cycle performance of the ternary positive electrode material on the one hand, and on the other hand reducing the requirements of the ternary positive electrode material on environmental humidity during use, thereby improving the storage performance of the ternary positive electrode material. A lower residual alkali content facilitates the smooth completion of the coating process of the positive electrode sheet.

[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A ternary positive electrode material, characterized in that: The ternary positive electrode material comprises a positive electrode substrate and a coating layer coated on the surface of the positive electrode substrate. The chemical formula of the positive electrode substrate is Li a Ni x Co y Mn 1-x-y O2, wherein 1.01≤a≤1.2, 0.6<x<1, 0<y<0.1, the coating layer comprises boron nitride, the residual base LiOH content on the surface of the ternary positive electrode material is 0.04-0.20wt%, and the residual base Li2CO3 content is 0.03-0.20wt%; The coating layer further comprises lithium borate, the molar ratio of the positive electrode substrate, the boron nitride and the lithium borate is 100:0.02-0.5:0.03-0.5, and the boron nitride is amorphous; The preparation method of the ternary positive electrode material comprises: Step S1, in an atmosphere containing methane, subjecting a sol comprising a nickel source, a cobalt source, a manganese source, a lithium source, and a water-soluble carbon source to a first heat preservation treatment according to the ratio of elements in the ternary positive electrode material to obtain a heat preservation treatment material; Step S2, performing a second heat preservation treatment on the heat preservation treated material in an oxygen-containing atmosphere to obtain a positive electrode substrate; Step S3, dry-mixing the positive electrode substrate with the boron-containing precursor to obtain a dry mixture; Step S4, calcining the dry mixture in an inert gas atmosphere containing nitrogen or a reducing gas atmosphere containing nitrogen to obtain the ternary positive electrode material. Wherein, the temperature of the first heat preservation treatment is greater than the temperature of the second heat preservation treatment.

2. The ternary positive electrode material according to claim 1, characterized in that: The D50 particle size of the ternary positive electrode material is between 2.50 and 4.50 μm.

3. A method for preparing the ternary positive electrode material according to claim 1 or 2, characterized in that: The preparation method comprises: Step S1, in an atmosphere containing methane, subjecting a sol comprising a nickel source, a cobalt source, a manganese source, a lithium source, and a water-soluble carbon source to a first heat preservation treatment according to the ratio of elements in the ternary positive electrode material to obtain a heat preservation treatment material; Step S2, performing a second heat preservation treatment on the heat preservation treated material in an oxygen-containing atmosphere to obtain a positive electrode substrate; Step S3, dry-mixing the positive electrode substrate with the boron-containing precursor to obtain a dry mixture; Step S4, calcining the dry mixture in an inert gas atmosphere containing nitrogen or a reducing gas atmosphere containing nitrogen to obtain the ternary positive electrode material. Wherein, the temperature of the first heat preservation treatment is greater than the temperature of the second heat preservation treatment.

4. The preparation method according to claim 3, characterized in that: In the step S1, the volume content of methane in the methane-containing atmosphere is 10-50%.

5. The preparation method according to claim 4, characterized in that: The methane-containing atmosphere includes a mixed gas of methane, nitrogen, argon and helium.

6. The preparation method according to claim 3, characterized in that: The temperature of the first heat preservation treatment is 500-900°C.

7. The preparation method according to claim 3, characterized in that: The first heat preservation treatment time is 3 to 5 hours.

8. The preparation method according to claim 3, characterized in that: The process of forming sol includes: Mixing raw materials including the nickel source, the cobalt source, the manganese source, the lithium source, and the water-soluble carbon source to form a raw material solution; The raw material solution is subjected to evaporation of the solvent to form the sol.

9. The preparation method according to claim 8, characterized in that: The mass of the water-soluble carbon source is 0.1-5 wt % of the total mass of the metal source in the raw material solution.

10. The preparation method according to claim 8, characterized in that: The water-soluble carbon source is selected from any one or more of glucose, sucrose, citric acid and starch.

11. The preparation method according to claim 8, characterized in that: The total concentration of metal ions in the raw material solution is 1-15 mol / L.

12. The preparation method according to claim 8, characterized in that: The nickel source comprises a metal salt of divalent nickel, and the nickel source is selected from any one or more of nickel nitrate, nickel sulfate, nickel chloride, and nickel acetate.

13. The preparation method according to claim 8, characterized in that: The cobalt source includes a metal salt of divalent cobalt, and the cobalt source is selected from any one or more of cobalt nitrate, cobalt sulfate, cobalt chloride, and cobalt acetate.

14. The preparation method according to claim 8, characterized in that: The manganese source includes a metal salt of divalent manganese, and the manganese source is selected from any one or more of manganese nitrate, manganese sulfate, manganese chloride, and manganese acetate.

15. The preparation method according to claim 8, characterized in that: The lithium source is selected from any one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium chloride, lithium phosphate, and lithium hydrogen phosphate.

16. The preparation method according to claim 8, characterized in that: The temperature of the evaporating solvent is 40-90°C.

17. The preparation method according to claim 8, characterized in that: The time for evaporating the solvent is 1 to 24 hours.

18. The preparation method according to any one of claims 3 to 17, characterized in that: In step S2, The temperature of the second heat preservation treatment is 300-600°C.

19. The preparation method according to any one of claims 3 to 17, characterized in that: The second heat preservation treatment time is 5 to 10 hours.

20. The preparation method according to any one of claims 3 to 17, characterized in that: The oxygen volume content in the oxygen-containing atmosphere is 30-99.9%.

21. The preparation method according to any one of claims 3 to 17, characterized in that: In the step S3, the dry mixing is performed by coating with a fluidized bed jet mill, and the conditions for coating with the fluidized bed jet mill are as follows: the carrier gas includes argon, carbon dioxide and nitrogen, the volume content of carbon dioxide in the carrier gas is 1-20%, the water content of the carrier gas is 1000-5000 ppm, the gas flow rate is 100-20000 mL / min, and the dry mixing time is 1-5 min; Calculated in terms of boron element, the molar number of the boron-containing precursor is 0.05-1% of the total molar number of metal elements in the positive electrode substrate.

22. The preparation method according to claim 21, characterized in that: The boron-containing precursor is selected from any one or more of boric acid, boron trioxide and ammonia borane.

23. The preparation method according to any one of claims 3 to 17, characterized in that: In the step S4, the calcination temperature is 300-600°C.

24. The preparation method according to claim 23, characterized in that: The calcination time is 1 to 5 hours.

25. A positive electrode, comprising a positive electrode material, characterized in that: The positive electrode material comprises the ternary positive electrode material according to claim 1 or 2.

26. A lithium ion battery comprising a positive electrode and a negative electrode, characterized in that: The positive electrode is the positive electrode according to claim 25.

Citation Information

Patent Citations

  • Interface composite modification method of positive electrode material, positive electrode material and application

    CN114014381A